The effect of doxycycline on canine hip osteoarthritis: design of a 6-months clinical trial - Nganvongpanit K. (2014)
Twenty-five dogs were included in a randomized, double-blind trial to assess the efficacy of doxycycline (DOX) orally administered twice a day at 4 mg/kg/day (n = 12) for the treatment of osteoarthritis of the hip. Chondroitin sulfate (CS; 525 mg/day) was used as a positive control (n = 13). Dogs were re-examined monthly for 6 months after initiation of treatment. The assessment protocol included clinical score, radiographic findings and serum osteoarthritis biomarkers. Dogs treated with DOX showed statistically significant improvements (p < 0.05) in lameness, joint mobility, pain on palpation, weight-bearing and overall score at 2, 6, 4, 4 and 4 months, respectively, after treatment. Biomarker levels of CS-WF6 epitope and hyaluronan were significantly increased and decreased (p < 0.05) at 2 and 3 months after treatment compared to pretreatment. These results showed that DOX had a positive therapeutic effect in dogs with osteoarthritis.